Pengembangan Media Pembelajaran Berbasis Website pada Mata Pelajaran Pengelolaan Rapat - Azrah Maysa Putri; Dewi Nurmalasari; Bayu Suhendry (Universitas Palangka Raya, 2026)
This study aimed to develop and evaluate the quality of website-based learning media using Google Sites for Meeting Management at SMKN 44 Jakarta. Method is based on Research & Development (R&D) using the ADDIE development model. Data were compiled through observation, questionnaires, and summative test, which were analyzed using descriptive qualitative and quantitative methods. Media quality testing was conducted by subject matter expert, media expert, and instructional design expert, as well as 45 students from 11th-Grade of Office Management. Results of the study proven that the learning media: 1) was highly valid with an average validity test score of 90.32%, 2) was highly practical with an average practicality test score of 95.74%, and 3) was highly effective in enhancing students’ understanding, as evidenced by an increase in the average score from 68.20 on the pre-test to 91.86 on the post-test with an N-Gain score of 0.74.